STRATEGI PENGEMBANGAN FASILITAS OBJEK WISATA AIR TERJUN SERASAH BETUNG PASAMAN BARAT - Riskinta, Pioma (RC-INSTITUT, 2019)
This research originated from observations of researchers on facilities in the form of supporting facilities in the tourist attraction of West Pasaman Serasah Betung Waterfall which is still very limited. With the huge potential possessed by the Object of Serasah Betung Waterfall while the problem is the availability of facilities in the form of limited supporting facilities in the Serasah Betung West Pasaman Waterfall Attractions. This study aims to describe how the strategy of developing West Pasaman Waterfall tourist facilities. This study consists of one indicator, namely: Supporting Facilities consisting of three sub-indicators, namely: Mushalla, Toilet and Trash. This type of research is a qualitative descriptive study with a survey method. The data source sample from this study is the tourist attraction manager, the community around the tourist attraction around the West Pasaman Serasah Betung Waterfall and visitors to the West pasaman serasah Waterfall tourist attraction. The sample collection technique uses purposive sampling. Data collection techniques are carried out by observation, interviews, and documentation. Furthermore, the data were analyzed by the Miles and Huberman data analysis techniques by performing three stages, namely: data reduction, data display and conclusion drawing.The results of the study concluded that in general the tourist attraction of West Pasaman Barat serasah waterfall has the strength to support the development of facilities in the form of place manager support by providing direction for the community.Weaknesses in the condition of human resources that have less role in the management and development of this attraction in West Pasaman Serasah Waterfall. Whereas the opportunities of the Serasah Betung Waterfall in West Pasaman add to regional income and are more recognized by the wider community. But there is also a threat, there are similarities in other tourist objects that are close to the attractions of West Pasaman Serasah Betung Waterfall and have more complete facilities. if no effort is made to maintain and improve the quality of this tourist attraction, the level of visits of tourists visiting this attraction will decrease. So it is necessary to do a strategy to develop the facilities of the tourist attraction in West Pasaman Serasah Waterfall